Effect of movement velocity during resistance training on muscle-specific hypertrophy: A systematic review. Issue 4 (21st April 2018) - Hackett, Daniel A.; Davies, Timothy B.; Orr, Rhonda; Kuang, Kenny; Halaki, Mark
Abstract: Currently, it is unclear whether manipulation of movement velocity during resistance exercise has an effect on hypertrophy of specific muscles. The purpose of this systematic review of literature was to investigate the effect of movement velocity during resistance training on muscle hypertrophy. Five electronic databases were searched using terms related to movement velocity and resistance training. Inclusion criteria were randomised and non-randomised comparative studies; published in English; included healthy adults; used dynamic resistance exercise interventions directly comparing fast training to slower movement velocity training; matched in prescribed intensity and volume; duration ≥4 weeks; and measured muscle hypertrophy. A total of six studies were included involving 119 untrained participants. Hypertrophy of the quadriceps was examined in five studies and of the biceps brachii in two studies. Three studies found significantly greater increases in hypertrophy of the quadriceps for moderate-slow compared to fast training. For the remaining studies examining the quadriceps, significant within-group increase in hypertrophy was found for only moderate-slow training in one study and for only fast training in the other study. The two studies that examined hypertrophy of the biceps brachii found greater increases for fast compared to moderate-slow training. Caution is required when interpreting the findings from this review due to the low number of studies, hence insufficient data. Future longitudinal randomised controlled studies in cohorts of healthy adults are required to confirm and extend our findings.